Environmental regulation, low-carbon technology progress and energy efficiency - Yu, Yingjing; Shi, Junwei (Frontiers in Environmental Science, 2022)
Low-carbon technological progress is an important way to achieve energy conservation and emission reduction, as well as achieve the goal of peaking carbon emission and carbon neutrality. Due to the difference in energy input structure, the difficulty of attaining low-carbon technology progress in industries with different energy consumption levels will lead to different responses to environmental regulation, affecting energy efficiency. This paper demonstrates the theoretical mechanism of how environmental regulation affects energy-saving efficiency through low-carbon technological progress in industries with different energy consumption levels. By reconstructing energy consumption of different industries in each province, this paper estimates the low-carbon technology progress in high-energy-consuming industries and low-energy-consuming industries in 30 provinces and cities of China from 2000 to 2016. It carries out empirical tests using mediating effect model. The results show that nationwide, the impact of environmental regulation on energy efficiency through low-carbon technology progress is U-shaped. Low-carbon technology progress accelerates the inflection point, indicating that the progress of low-carbon technology is beneficial for strict environmental regulation policies to improve energy efficiency. It shows there is asymmetric regional heterogeneity in the impact of environmental regulation on energy efficiency through low-carbon technology progress in high-energy-consuming and low-energy-consuming industries: in the central-western region, the progress of low-carbon technology in high-energy-consuming industries is faster than that in low-energy-consuming industries; in eastern region, room for energy-saving through low-carbon technology in low-energy-consuming industries is more significant than that in high-energy-consuming industries. This paper provides empirical evidence and policy suggestions for China to implement differentiated environmental regulation policies in accordance with local conditions, promote green technology transformation, and conserve the ecological civilization.